Academic Adjustment as a Mediator of Self-Effficacy in Online Learning and Subjective Well-Being in Students - Husnul Dwinanda; Sumedi P Nugraha (Psychosophia: Journal of Psychology, Religion, and Humanity, 2023)
The widespread and rapid spread of the COVID-19 pandemic has made the offline learning to be changed to online learning from home. It subsequently has brought on impact on the subjective well-being of students. This study was aims to examine to what extent the role of self-efficacy in online learning and academic adjustment can predict the level of subjective well-being of students at Islamic University of Indonesia during the COVID-19 pandemic. A number of previous studies have shown that students with good self-efficacy and academic adjustment will have good subjective well-being. Research data were collected using the PANAS (Positive Affect and Negative Affect Scale) scale from Watson, Clark, and Tellegen and the SWLS (Satisfaction with Life Scale) scale from Diener to measure the affective components or positive and negative experiences of the respondents; self-efficacy scale in online learning from Zimmerman and Kulikowich; and the academic adjustment scale of Anderson, Guan, and Koc. Data analysis was conducted using exploratory factor analysis (EFA) and mediation analysis using JASP 0.16.1 software. The results of the analysis showed that self-efficacy in online learning brought an impact on the students' subjective well-being during the COVID-19 pandemic through the intermediary of academic adjustment (0.055). Individuals with high self-efficacy in online learning will be capable of adjusting to adjust to online academic demands well. It, as a result, has brought an impact on the quality of good subjective well-being. Thus, the research hypothesis is accepted.